2013
DOI: 10.1007/s10067-013-2438-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and cost-effectiveness of carpal tunnel injections using sonographic needle guidance

Abstract: This randomized controlled study addressed whether sonographic needle guidance affected the outcomes of corticosteroid injection for symptomatic carpal tunnel syndrome. Seventy-seven symptomatic carpal tunnels were randomized to injection by either (1) conventional anatomic landmark palpation-guided injection or (2) sonographic image-guided injection, each using a two-step technique where 3 ml of 1% lidocaine was first injected to hydrodissect and hydrodisplace critical intra-carpal tunnel structures followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 55 publications
0
38
0
1
Order By: Relevance
“…Therefore, injection under ultrasound (US) guidance may increase precision and therapeutic outcomes and decrease complication rates. There are only a few studies that have investigated US guidance for injections in CTS, and they generally determined that US-guided injections result in better symptom relief and increased and long-lasting therapeutic effects compared to blind injections (11)(12)(13). Since the studies in this area are limited in number, this study was conducted to compare the effectiveness of USguided injection versus blind injection of corticosteroids in the treatment of severe CTS according to symptom severity, hand function, and electrophysiological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, injection under ultrasound (US) guidance may increase precision and therapeutic outcomes and decrease complication rates. There are only a few studies that have investigated US guidance for injections in CTS, and they generally determined that US-guided injections result in better symptom relief and increased and long-lasting therapeutic effects compared to blind injections (11)(12)(13). Since the studies in this area are limited in number, this study was conducted to compare the effectiveness of USguided injection versus blind injection of corticosteroids in the treatment of severe CTS according to symptom severity, hand function, and electrophysiological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies evaluated injections into a single structure (42/49 (86%)),17 51 54 69 80 84–87 90–95 97–101 103–113 115–125 but seven studies (14%) investigated injections into more than one structure 52 71 88 89 96 102 114. In decreasing frequency, studies evaluated injections into bursae (19/49 (39%)),17 51 52 54 69 87 91–93 95 97 100 101 103 105 110 115 121 123 tendon sheaths (9/49 (18%)),71 89 102 106 108 111–113 116 tendons or fascia (8/49 {(16%)),96 102 107 112 119 120 124 125 perineural regions (6/49 (12%)),85 88 94 104 109 122 muscles (5/49 (10%)),86 97 114 117 118 cysts (2/49 (4%)),84 90 peritendinous regions (2/49 (4%)),71 102 wounds (1/49 (2%))52 and periarticular spaces (1/49 (2%)) 80…”
Section: Resultsmentioning
confidence: 99%
“…Advancements in ultrasonography allow the visualization of the structures of the carpal tunnel, including the median nerve, flexor tendons, and the TCL as well as the structures at risk, including the ulnar artery and the proximal palmar arch. Recent studies have demonstrated that corticosteroid injection with the use of ultrasound guidance is better than blind administration and reduces the time to symptom resolution [1,8,12,13]. However, ultrasound can clearly delineate the needle and dynamically observe the puncture process; thus, the authors designed the technique of combined use of ultrasound-guided local corticosteroid injections and needle release.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a real-time anatomic, high-resolution image of the median nerve, the carpal tunnel, and the neighboring structures, and helps physicians to place the needle tip and inject closer to the median nerve accurately. Several previous studies have demonstrated higher effectiveness of ultrasound-guided injections in CTS when compared to blind injections [1,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%